(untitled) (Environment & Health, 2023)
Objective: Epidemiological assessment of the risks of developing non-neoplastic diseases of the digestive organs in evacuees from the 30-kilometer zone of the Chornobyl nuclear power plant in 1992–2016, analysis of the impact of ionizing radiation in small doses. Materials and methods: Epidemiological studies were conducted in a cohort of 4501 adults evacuated from the 30-kilometer zone of the Chornobyl nuclear power plant, with the presence of reconstructed effective doses of external ionizing radiation in the range of 0.001 Sv ÷ 0.38 Sv. The total cohort of subjects was stratified into 2192 individuals with exposed doses in the range of 0.001 Sv ÷ 0.05 Sv (IG) (internal control) and 2.309 individuals with exposed doses in the range of 0.051 Sv ÷ 0.38 Sv (EG). Epidemiological indicators used are absolute risk (AR), relative risk (RR) with 95% (±CI) confidence intervals (changes in risk values at the level of significance (p